(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The article analyzes the historical situation, socio-economic situation and spiritual-cultural development in Movarounnahr and Khurason in the 15th-16th centuries. The spiritual life of this period was studied on the basis of primary sources, and its influence on the formation of the worldview of Alloma Fakhruddin Ali Safi was evaluated.